THE STUDY ON HYPOGLYCEMIC EFFECT OF UNLEAVENED CRUSTLESS BREAD - Solodnikov S.Y.; Lyushina G.A; Maslova V.V. (Техника и технология пищевых производств, 2016)
Type 2 diabetes has a stead tendency to increase all over the world. A balanced diet is the foundation of success in improvement of life quality of patients suffering from diabetes. The restriction of consumption of such foods as bread requires the development of formulations and techniques for baking bread, which will minimally raise blood glucose level and preserve the optimal amount of amino acids and vitamins in bread. One way to obtain bread with a low glycemic index is a crustless bread production technology with electrocontact method, while using it the crust of bread is not formed, and the temperature and baking time are minimal now. The effects of «Rye unleavened crustless bread» that was produced with electrocontact method (SP «Goncharova O.N.») in comparison with «Rye diet bread», that was produced with the traditional technology - radiation-convective method (JSC «Pokrovsky bread») on the blood glucose level of white rats at unitary and systemic intake has been studied. It was found that a hypoglycemic effect was not observed under one-time intake of bread in both cases. It was established that blood glucose level started to lower earlier in animals systematically treated with the «Rye unleavened crustless bread» as compared to animals treated with «Rye diet bread». This allows us to recommend «Rye unleavened crustless bread» as a dietary food for people with diabetes and people living a healthy lifestyle.